The Commonwealth of nations and ‘francophone’ Africa: bridging the colonial divides? - (:unkn) unknown (My University, 2023)
This chapter discusses to what extent and why cooperation between the Commonwealth of Nations and Francophonie, since it first emerged as the Agence de coopération culturelle et technique (ACCT) at Niamey in 1970, has helped bridge the divide between French-speaking and English-speaking Africa and the various barriers left by European colonial rule. Beyond differences, both the Commonwealth and Francophonie in its various iterations have been a means for African states to manage relations with the ex-colonial power – even when the current Organisation Internationale de la Francophonie, with its 88 members, provides a very different geography from that of the former French (or Belgian) empire. From democracy, human rights and the rule of law to security and development, the evolution of the two organizations shows that while there has been a marked improvement in relations and in the reconfiguration of identities as constructed under empire, distinct institutional cultures remain strong and limit political initiatives, notably in Africa.
Keywords: African Research